Effect of school feeding program on dietary folate intake among school adolescent girls in Sidama region, southern Ethiopia - Bolka, Amelo; Bosha, Tafese; Gebremedhin, Samson (Frontiers in Nutrition, 2024)
Background: Ethiopia recently initiated a school feeding program (SFP) that provides nutritious meals to vulnerable students during school to combat malnutrition and improve their nutrition. However, there is limited evidence regarding the program's impact on dietary folate intake among adolescent girls. Improving folate status in adolescent girls is important to prevent neural tube defect and anemia This study was aimed at assessing the effect of the SFP on dietary folate intake among school adolescent girls in the Sidama Region, Southern Ethiopia.Methods: This school-based cross-sectional study compared dietary folate intake among adolescent girls enrolled in schools with (n =290) and without (n =290) SFP. Multistage sampling method was used to select adolescent girls from 12 schools. The multiple pass 24hour dietary recall method was used to estimate the dietary intake of adolescent girls. Dietary diversity in the preceding day of the survey was assessed with the standard nine-food group score. Nutrient inadequacy was defined as a proportion of adolescents with dietary value of nutrient intake less than the recommended daily allowance (RDA). The dietary folate intake was compared between two groups using multilevel mixed effects linear regression model adjusted for potential confounders.The result showed significantly higher mean (±SD) dietary folate intake in SFP beneficiaries (421.12 ± 78.60 μg/day) than the non-beneficiaries (393.26 ± 74.57 μg/day) (β = 27.19, p < 0.001). SFP beneficiary girls had a significantly higher mean (±SD) dietary diversity score (5.24 ± 1.35) compared to non-beneficiary girls (4.83 ± 1.54) (β = 0.40, p = 0.001). The prevalence of inadequate folate intake was significantly higher among nobeneficiaries (47.4%) compared to beneficiaries (36.9%) (P = 0.01).The SFP in Sidama region improved folate intake and dietary diversity of adolescent girls. The evidence from this study supports the expansion of the program to enhance dietary intake of nutrients of adolescent girls in the region.